Influence of subglacial conditions on ice stream dynamics: Seismic and potential field data from Pine Island Glacier, West Antarctica. Issue 4 (15th April 2013) - Smith, Andrew M.; Jordan, Tom A.; Ferraccioli, Fausto; Bingham, Robert G.
Abstract : [1] We interpret seismic reflection and airborne potential field data acquired on Pine Island Glacier, West Antarctica and find variations in the subglacial geology which correlate with variations in ice dynamics. Immediately beneath the glacier is a mixture of soft, deforming sediments and harder, non‐deforming sediments. Beneath this, a sedimentary basin lies under part of the main glacier, with another under one of its slower‐moving tributaries. A tectonic boundary underlies the main trunk of the glacier separating these sedimentary basins to the north from crystalline rocks to the south, which also include a thick, rift‐related magmatic intrusion. The boundary correlates with changes in the basal roughness, ice flow speed, and basal drag. Smoother bed, faster flow, and lower basal drag characterize the thicker sedimentary sequences, to the north, but there is no corresponding lateral change in the acoustic properties of the bed. Changes in the sub‐bed (i.e., deeper than the ice‐bed interface) lithology appear to account for the contrasting basal drag and ice velocity patterns over the glacier. Subglacial erosion could remove a thin layer of soft sediments to the south of the geological boundary, leading to increased basal drag and reduced ice flow in the future. We conclude that the subglacial geology plays a significant role in controlling the spatial pattern of present‐day ice flow and that the consequences of subglacial erosion may be reflected in temporal changes to the ice dynamics in the past and perhaps also in the near future. Key Points: Ice flow variations are controlled by subglacial geology Continued subglacial erosion could result in a reduction in ice flow Better knowledge of subglacial geology required for future ice sheet predictions